2003
DOI: 10.1081/iph-120020467
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Superoxide Production in EL4 Lymphoma Cells Overexpressing Growth Hormone

Abstract: A substantial body of research exists to support the production of growth hormone by cells of the immune system. However, the function and mechanism of action of lymphocyte-derived growth hormone remain largely unelucidated. Since, it has been found that exogenous growth hormone (GH) primes neutrophils for the production of reactive oxygen intermediates (ROI) and in particular superoxide (O2-), we investigated the role of GH on the production of O2- in T cells. Furthermore, we examined whether endogenous and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In contrast, restoration of the episodic GH profile had a suppressive effect on thymic and splenic CY2C11 expression in both sexes suggesting a substantial difference in the regulation of the isoform by GH between the liver and that of the thymus and spleen. In this regard, CYP2E1 activity in liver is increased by GH [12,15], but in lymphoma cells was found to be suppressed by GH [40]. Incidentally, the fact that circulating GH (i.e., pituitary) can regulate CYP2C11 expression in thymus and spleen does not preclude, but rather supports the possibility that lymphocyte-derived GH may also regulate expression of the isoform in the immune system.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, restoration of the episodic GH profile had a suppressive effect on thymic and splenic CY2C11 expression in both sexes suggesting a substantial difference in the regulation of the isoform by GH between the liver and that of the thymus and spleen. In this regard, CYP2E1 activity in liver is increased by GH [12,15], but in lymphoma cells was found to be suppressed by GH [40]. Incidentally, the fact that circulating GH (i.e., pituitary) can regulate CYP2C11 expression in thymus and spleen does not preclude, but rather supports the possibility that lymphocyte-derived GH may also regulate expression of the isoform in the immune system.…”
Section: Discussionmentioning
confidence: 96%
“…As most of the GH produced by lymphocytes remains intracellularly, Farmer and Weigent [253] considered the ability of endogenous GH to induce TGF-b1 was due to an autocrine or intracrine action mediated within the cell. Endogenous GH in the same lymphocyte cells was also found to enhance the production of nitric oxide (NO), most likely by a mechanism that involved an increase in the synthesis of nitric oxide synthase and an increase in the transport of arginine, leading to enhanced cell survival [254]. The overexpression of GH in these lymphoma cells also results in a decrease in the production of superoxide (O 2 -) which also protects them from apoptosis [254].…”
Section: Gh In Cancersmentioning
confidence: 95%
“…Endogenous GH in the same lymphocyte cells was also found to enhance the production of nitric oxide (NO), most likely by a mechanism that involved an increase in the synthesis of nitric oxide synthase and an increase in the transport of arginine, leading to enhanced cell survival [254]. The overexpression of GH in these lymphoma cells also results in a decrease in the production of superoxide (O 2 -) which also protects them from apoptosis [254]. The antiapoptotic action of GH overexpression is also due to a decrease in the expression of bax, BAD, and caspases 3, 8, and 9 and by an increase in BcI 2 production.…”
Section: Gh In Cancersmentioning
confidence: 96%
“…However, GH had no effect on the expression of NADPH oxidase subunits. Although there is no report about the protective action of GH on local oxidative stress in glomeruli, many studies have demonstrated that GH indeed has beneficial effect on oxidative stress-associated injury in other tissues or organs such as heart, vessels and lymphocytes [12,43,49]. To address the functional significance of GH-induced suppression of EMT in podocytes, we determined the role of GH in Hcys-induced enhancement of podocyte monolayer permeability.…”
Section: Discussionmentioning
confidence: 99%